Portugal no conselho de segurança das Nações Unidas - Caleiras, João Fernendo de Sousa (2016)
The United Nations is an international organization that was created after World War II, whose main objective is to promote cooperation, social and economic development, as well as to ensure international peace and security. The Member States are key actors in the international political system. For that reason they have strategic interests in what regards taking part in the international organizations. They see it as an opportunity to achieve those goals. The United Nations Security Council has a very important role in preserving international peace and security. It is the organ of the United Nations in which fifteen member states are represented: five permanently and ten non-permanently, being that the latter are elected for two years. Participating in the Security Council is a unique opportunity for middle powers like Portugal to promote their national interests and to increase their international visibility. In addition, they can contribute to the world’s destiny during their mandate period. Portugal has exercised his third term as a non-permanent member of the Security Council in 2011-2012 biennium, defeating Canada after a successful campaign carried out by the Portuguese diplomacy. This study analyses the participation of Portugal in the Security Council´s 2011-2012 biennium. It will focus the application process and election and the role of Portugal in the Security Council, especially in its the presidency and its intervention in the presidency of the Sanctions Committee on Libya. Its aim is to show the impact of Portuguese participation in the Security Council for international peace and security, as well as the geopolitical importance for the country of being part of the Security Council.